Pendampingan Proses Produk Halal (PPH) dalam Program Sertifikasi Halal Gratis (SEHATI) pada Produk Keripik Pare Bunda - Devid Frastiawan Amir Sup (An Naf'ah: Jurnal Pengabdian Masyarakat, 2023)
Muslims want every product to have halal certification, meaning that it has met the eligibility standards and is in accordance with the halal requirements of a product according to the Islamic religion. The first phase of the mandatory halal certificate will end on October 17, 2024. There are 3 (three) groups of products that must have halal certification as the first phase ends, food and beverage products, raw materials, food additives, and supporting materials for food products and beverages, as well as slaughter products and slaughter services. PPH assistance is an activity to assist micro and small business actors in fulfilling the requirements for a product halal statement. The business actor who is assisted is Mrs. Murtiningsih, with a type of product in the form of fruits and vegetables with processing and addition of food additives with the trademark Bunda. In applying for this halal certification, Mrs. Murtiningsih experienced difficulties in using a computer/laptop and the internet. The assistance method used is collecting data on business actors, product identification, identifying ingredients used in products, compiling production process flows, submitting data via the https://ptsp.halal.go.id page, verifying and validating data by the PPH Assistant, and monitoring the status of the application until a halal certificate is issued. Based on the results of the assistance provided, the product is declared to meet the requirements to obtain a halal certificate from the SEHATI Program. The process of applying for this halal certification began on October 24, 2022 and a halal certificate was issued on April 05, 2023 with certificate number ID35110001696301122 with a validity period until April 05, 2027.